Comparative morphological and molecular taxonomic study of six Achaeta species (Clitellata: Enchytraeidae) with the description of a new Achaeta species from Kőszeg Mountains, Hungary - Dózsa-Farkas, Klára; Felföldi, Tamás (Zootaxa, 2017)
Five Achaeta species (A. affinis, A. bohemica sensu stricto, A. camerani, A. cf. danica, A. unibulba) and a new species, described here as A. tothi sp. n., were found during the investigation of the enchytraeid fauna of western Hungary (Őrség National Park and Kőszeg Mts.). Comparative morphological and molecular taxonomic investigations were performed with several individuals representing these six Achaeta species. A detailed description of the new species is given, and we also present some additional morphological data and photos about the other five Achaeta species. Such information could have importance in subsequent taxonomic studies and will aid the discrimination among the members of genus Achaeta. Furthermore, the obtained sequences could serve as references in forthcoming studies applying DNA-based taxon identification.